Mitraria Learning Media to Stimulate Critical Thinking Skills in Children Aged 5-6 Years - Ajeng Larasati; I Wayan Sutama; Nur Anisa (Jurnal CARE (Children Advisory Research and Education), 2026)
The 21st century demands 4C skills, including critical thinking, but these skills are still low in children aged 5–6 years, such as in Bintang Pertiwi Kindergarten and Pembina Bengalon 1 Kindergarten. Teacher-centered learning models and the lack of interactive media influence this condition. This study aims to develop and test the feasibility of an Android-based educational game, Mitraria, to stimulate children's critical thinking. The method used is R&D with the ADDIE model. In small group trials and also large group trials that researchers conducted on May 30–June 6, 2025, the Mitraria game showed a significant increase in results. Based on the trial results in this study, it states that the Mitraria game is very suitable/feasible and effective for use as an alternative medium to stimulate critical thinking skills in children aged 5–6 years, as well as providing an interactive, fun, and relevant learning experience with technological developments.